2018
DOI: 10.1016/j.scs.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Improving pedestrian level low wind velocity environment in high-density cities: A general framework and case study

Abstract: A B S T R A C TAn acceptable pedestrian level wind environment is essential to maintain an enjoyable outdoor space for city residents. Low wind velocity environment can lead to uncomfortable outdoor thermal experience in hot and humid summer, and it is unable to remove the pollutants out of city canyons. However, the average wind velocity at pedestrian level is significantly lowered by closely spaced tall buildings in modern megacities. To improve the low wind velocity environment at pedestrian level in high-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 77 publications
0
16
0
2
Order By: Relevance
“…Through a wind tunnel experiment on the campus of the Hong Kong Polytechnic University, Du and Mak demonstrated that pedestrian-level wind comfort is greatly improved with the adoption of measures such as opening and lift-up [3]. Tes et al analyzed the impact of lift-up building models with different core heights and widths on surrounding wind environments [24].…”
Section: Combination Of the Permeable Railing And Lift-up Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Through a wind tunnel experiment on the campus of the Hong Kong Polytechnic University, Du and Mak demonstrated that pedestrian-level wind comfort is greatly improved with the adoption of measures such as opening and lift-up [3]. Tes et al analyzed the impact of lift-up building models with different core heights and widths on surrounding wind environments [24].…”
Section: Combination Of the Permeable Railing And Lift-up Designmentioning
confidence: 99%
“…With the rapid development of urbanization in China, land resources are becoming increasingly scarce, and building density and height in urban residential districts are rapidly increasing [1,2]. High-density residential districts exhibit reduced ventilation and heat dissipation conditions, thus leading to low wind velocity environments and poor thermal comfort in residential districts [3]. This problem is particularly serious in summer, especially in the densely populated eastern coastal areas of China [4].…”
Section: Introductionmentioning
confidence: 99%
“…In doing this, computer modeling methods have been widely accepted as a key technique (Robinson, 2012). Martins et al (2016) investigated the influence of resilient urban design strategies on outdoor climate and pedestrian thermal comfort; Du and Mak (2018) explored the influence on pedestrian level wind environment. Aschwanden (2014) and De Nazelle (2007) examined the impact of active travel plans on local air pollution and walking behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The geometric characteristics of the building can change the airflow pattern at the pedestrian level (Gao et al, 2012). The pedestrian-level wind environment should be simulated during the specific architectures that are designed (Du and Mak, 2018). The architectural design of the overhead floor was a way to reduce the weakening of the wind environment to the surrounding open space (Du and Mak, 2018).…”
Section: Wind Environment Changes In Open Spacesmentioning
confidence: 99%
“…The pedestrian-level wind environment should be simulated during the specific architectures that are designed (Du and Mak, 2018). The architectural design of the overhead floor was a way to reduce the weakening of the wind environment to the surrounding open space (Du and Mak, 2018). This study included high-rise buildings and even super high-rise buildings of up to 450m.…”
Section: Wind Environment Changes In Open Spacesmentioning
confidence: 99%